Acartia (Odontacartia) ohtsukai Ueda and Bucklin, 2006 (Copepoda, Calanoida, Acartiidae): First Record of its Occurrence in Korean Waters and Habitat Segregation from its Sibling Species A. pacifica Steuer, 1915 - Moon, Seong-Yong; Ohtsuka, Susumu; Ueda, Hiroshi; Soh, Ho Young (Zootaxa, 2008)
Species of the genus Acartia Dana, 1846 (Copepoda, Calanoida, Acartiidae) are predominant and widespread in estuarine and coastal waters worldwide, but the spatio-temporal distribution of each species is very restricted (Bradford 1976). Acartia pacifica Steuer, 1915 has been recognized as a common species in euryhaline waters on the Korean coasts from summer to fall (Suh et al. 1991; Soh & Suh 1993; Park 2005). Recently, Ueda and Bucklin (2006) described A. ohtsukai from low saline waters in the Ariake Sea, Western Japan, which has been confused with A. pacifica s. s. on the basis of their morphological and genetic differences (0-3% in mtCOI sequences). According to Ueda and Bucklin (2006), A. ohtsukai has a restricted distribution in continental brackish waters of East Asia with a relict population in the Ariake Sea, while A. pacifica is broadly distributed in coastal waters in the tropical/subtropical Indo-West Pacific regions. During our investigation of planktonic copepods A. ohtsukai was recorded in Korean waters for the first time. This species may have been confused in the past with its sibling species A. pacifica by Korean researchers. Therefore, we compare the spatio-temporal distributions of A. pacifica and A. ohtsukai in Gwangyang Bay, southern Korea.